New species of Senecio (Asteraceae, Senecioneae) from Southern Peru - Beltrán, Hamilton (2017)
Senecio sagasteguii and Senecio qosqoensis (Asteraceae, Senecioneae), two new species from Cusco region, in southeastern Peru, are described and illustrated. Both new taxa are assigned to Senecio section Senecio series Chilenses subseries Caespitosi by its subshrubby habit and solitary or few discoid capitula. Some remarks on their possible morphological affinities, geographical distribution, and ecological preferences are supplied.